Urgensi Syajarah Al-Mirats dalam Penerapan Ayat Mawarits di Era Kontemporer - Rasyida Arsjad (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
If Faraidh Science is not implemented and practiced, it is like plants that die due to pest even disappear all time. The changing of civilization and epoch making a Faraidh experts who consist in their studies are missing from the treasury of scientific successor. Study of science in the modern era bears the contemporary sciences rapidly. But science that is assigned by Allah directly through His texts are found rarely to be explored and used as a very important science icon to be studied, especially in the contemporary era rigth now. An Islamic Inheritance law brought by Prophet Muhammad SAW has transformed the Arab inheritance law pre-Islamic era and restructure family links simultaneously, even restructure the public ownership system overhaul in the property, especially the inheritance. Allah detailing and explaining the portion of each heir through the Qur'an with the goal of achieving justice in society. However, until recently the portion of inheritance issues still causing family rift because of human avarice and greed. Through Syajarah Al-Mirats (Inheritance Trees) is expected to facilitate scientists and lovers of knowledge continue to explore the science of mawarits which is half of the science.